THE PASHА’S CONCUBINE – A VICTIM AND A WITNESS (Heritage, 2023)
As an authentically religious protagonist who values her life in terms of sin and punishment, Mara the concubine stands out from the entire gallery of Andrić’s female characters. In the context Andrić hinted at through his analogous portraits of Mara and Nevenka, we compare the different reaction of these heroines to the evil they see and suffer: Mara soaks the world in as if through osmosis, and although she tries to flee from evil, she cannot stop the gradual but inevitable development of mental illness. Revictimized in her social surroundings, with reinforced feelings of guilt and without support in the church, Mara loses her mind. Mara is unambiguously a victim of evil, but she also appears as its silent witness, which gives her fate an extraordinary quality. By placing the suffering Mara in the position of a silent witness, Andrić points to her high level of empathy: as a listener, Mara helps Nevenka become and remain the agent in her own life and story. There is no dark side to the protagonist, she suffers her fate as a sensitive being completely void of negative emotions who senses that hatred transforms the victim into someone who perpetuates evil in the world.We have also demonstrated the compensatory role of Mara’s dream, which she dreams right before the last strike that would be inflicted on her. The dream reminds the protagonist of her own worth which is of heavenly nature: the dream emphasizes the symmetry of the macrocosmos and the microcosmos, as well as the unbroken dialogue of the self with God, despite Mara’s conscious conviction and emotion of being an isolated outcast.
Keywords: Ivo Andrić, The Pasha’s Concubine, victim, witness, dream, violence